Modeling and Numerical Simulation of Semitensioned Mooring Line under Taut-Slack State - Ruizhi Shi; Suxia Zhang; Xijun Liu; Chong Tian (Shock and Vibration)
In this paper, considering the mooring system can be taut-slack in the motion, the dynamic equations of the mooring system are derived by using the theory of large deformation. The nonlinear dynamic response of semitensioned mooring line is numerically simulated. Assuming the platform motion is known, the effect of platform on mooring line is simplified as an end-point excitation. Directly using the finite difference method for numerically solving partial differential equations of mooring line, the dynamic responses can be obtained. Then, the causes about the nonlinear state are analyzed, and the location where the taut-slack phenomenon occurs can be located by calculating the tension of mooring. The results show that the mooring line is more likely to be taut-slack under tangential excitation with the tension change, while the mooring remains taut under normal excitation. The taut-slack state of the mooring line is concentrated near the anchor point. Through the amplitude-frequency curve and bifurcation point set, it is found that the taut-slack region is accompanied by multiperiod motion. And the taut-slack phenomenon will lead to the unstable motion.